2021
DOI: 10.1007/s13280-020-01481-y
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19: From health crises to food security anxiety and policy implications

Abstract: Like the rest of the world, African countries are reeling from the health, economic and social effects of COVID-19. The continent’s governments have responded by imposing rigorous lockdowns to limit the spread of the virus. The various lockdown measures are undermining food security, because stay at home orders have among others, threatened food production for a continent that relies heavily on agriculture as the bedrock of the economy. This article draws on quantitative data collected by the GeoPoll, and, fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(76 citation statements)
references
References 54 publications
1
69
0
Order By: Relevance
“…Our results on the food security of the studied population show that the main problems confronting rural families during the pandemic conditions are “could not afford to eat balanced meals” and “worried food would run out,” which is consistent with Elsahoryi et al [ 33 ] and Chiwona-Karltun et al [ 65 ]. Under COVID-19 conditions, most rural families are faced with problems of supplying appropriate food for their family members due to the quarantine, the restriction policies, and the inflation of food prices.…”
Section: Discussionsupporting
confidence: 90%
“…Our results on the food security of the studied population show that the main problems confronting rural families during the pandemic conditions are “could not afford to eat balanced meals” and “worried food would run out,” which is consistent with Elsahoryi et al [ 33 ] and Chiwona-Karltun et al [ 65 ]. Under COVID-19 conditions, most rural families are faced with problems of supplying appropriate food for their family members due to the quarantine, the restriction policies, and the inflation of food prices.…”
Section: Discussionsupporting
confidence: 90%
“…COVID-19 cut these relationships and limited people's access to nutritious foods through lockdown restrictions [87]. Numerous evidence indicated that general consequences of the pandemic in the agricultural sector, including labor shortages, reduction of planting and harvesting, and reduction of agricultural trade, created an imbalance in the food system of many countries [88][89][90]. Although ecological constraints, such as climate change, water crisis, and land degradation, could significantly damage the prospects for economic growth and lead to food insecurity [91].…”
Section: Covid-19 Challenges Toward Sustainable Agriculturementioning
confidence: 99%
“…Stability . Food stability emphasizes that all humans should have access to enough food all the time, regardless of any unforeseen risk (such as a pandemic), which could prevent people from accessing food [ 158 , 159 ].…”
Section: Covid-19 and Comorbiditiesmentioning
confidence: 99%